Diaphragm pacing in spinal cord injury can significantly decrease mechanical ventilation in multicenter prospective evaluation. Issue 10 (8th March 2022) - Onders, Raymond P.; Khansarinia, Saeid; Ingvarsson, Páll E.; Road, Jeremy; Yee, John; Dunkin, Brian; Ignagni, Anthony R.
Abstract: Background: Cervical spinal cord injury (SCI) can lead to dependence on mechanical ventilation (MV) with significant morbidity and mortality. The diaphragm pacing system (DPS) was developed as an alternative to MV. Methods: We conducted a prospective single‐arm study of DPS in MV‐dependent patients with high SCI and intact phrenic nerves. Following device acclimation, pacing effectiveness to provide ventilation was evaluated. The primary endpoint was the number who could use DPS to breathe for 4 continuous hours without MV. Secondary endpoints included the number of patients that could use DPS 24 h/day free of MV and the ability of DPS to maintain clinically acceptable tidal volume (Vt). In addition, we conducted a meta‐analysis that included the prospective study along with data from four recently published studies to evaluate DPS hourly use. Results: Fifty‐three patients were implanted in the prospective study. Most were male (77.4%) with a median time from injury to treatment of 28.3 (IQR: 12.1, 83.3) months. Four‐ and 24‐h use occurred in 96.2% (95% CI: 87.0%, 99.5%) and 58.5% (95% CI: 44.1%, 74.9%), respectively. Four and 24‐h results in the meta‐analysis cohort ( n  = 196) exhibited similar results 92.2% (95% CI: 82.6%, 96.7%) and 52.7% (95% CI: 36.2%, 68.6%) using DPS for 4 and 24 h, respectively. DPS use significantly exceeded the calculated basal tidal volume requirements by a mean of 48.4% (95% CI: 37.0, 59.9%; p  < 0.001). Conclusions: This study demonstrates that in most ventilator‐dependent patients, diaphragm pacing can effectively supplement or completely replace the need for MV and support basal metabolic requirements. Abstract : Diaphragm pacing decreases mechanical ventilation in spinal cord injured patients